Verify(a+b)+c =a(b+c) for each of the following. 

a) a=0, b=-19, c=-27

b)a=-138, b=-39, c=57.

Asked by shreyasonar94.7spicertl | 17th Jun, 2020, 06:50: PM

Expert Answer:

(i) a = 0, b = -19, c = -27
(a+b)+c = [0+(-19)]+(-27) = -19 - 27 = -46
a+(b+c) = 0+[-19+(-27)] = -19 - 27 = -46
Therefore, (a+b)+c = a+(b+c)
 
(ii) a = -138, b = -39, c = 57
(a+b)+c = [-138+(-39)]+57 = -138 - 39 + 57 = -177 + 57 = -120
a+(b+c) = -138+[(-39)+57] = -138 + 18 = -120
Therefore, (a+b)+c = a+(b+c)

Answered by Renu Varma | 18th Jun, 2020, 10:42: AM